The Effect of Rapid Response Teams on End-of-Life Care: A Retrospective Chart Review - Benjamin Tam; Mary Salib; Alison Fox-Robichaud (Canadian Respiratory Journal)
BACKGROUND: A subset of critically ill patients have end-of-life (EOL) goals that are unclear. Rapid response teams (RRTs) may aid in the identification of these patients and the delivery of their EOL care.